Menyoal Hermeneutika Feminis terhadap Wacana Kesetaraan Gender - Sayyaf Nasrul Islami (UIN Fatmawati Sukarno Bengkulu, Indonesia, 2022)
Until now, gender equality is still a hot topic for discussion among Muslim feminists. Via content analysis, this study tries not only to elaborate a number of products of the Hermeneutic model of the reinterpretation of the Koran the women's version but also shows the history of feminism ideology and the inappropriate use of hermeneutic interpretations. The initiators and advocates of gender equality often question Islamic law which is considered unfair in positioning men and women. Women are considered discriminated against by the products of Islamic law that have been established so far. From its historical background, feminism departs from the ideology of hatred as a form of resistance to the oppression of women that occurred in Western-Christian civilization in the past. Hermeneutic interpretation method also comes from the Christian academic tradition which considers the biblical text not as revelation. These two facts are diametrically opposed to the facts in the Islamic tradition. Islam actually came with the glory and majesty of its teachings. The change in the social position of women was no exception, which was more glorified when Islam changed the Arab civilization of ignorance at that time. The concept of equality is basically difficult to find in Islamic scholarship. Islam is more familiar with the term